(untitled) (Journal of Universal Excellence, 2026)
Research question (RQ): What are the effects of the environment and working life on quality of life? Purpose: Quality of life changes from year to year. The purpose and aim is to provide an overview of the current situation and to propose approaches to improvement. Method: In the study we used a qualitative method based on analytical study. It is based on the study of existing literature, articles and personal experience. Results: We have found that work is not a separate dimension from the other components of human life, but that working life also affects other aspects of an individual’s life. Organisation: The organisation and the state and the wider surrounding area are an integral part of the macro environment, and they can use their policy tosupport and encourage their society. Company: People need to balance their private lives and careers, potential earnings, spending time with their family, and the state should introduce them with the best possible living conditions. Originality: In the work we presented important factors that affect the quality of life and working life. They are the only one suitable to be exposed and analysed and proposals for improvement. Limitations/further research: We limited us to reviewing existing articles and content related to the impact of living and working environments on life. We could continue with research that would be upgraded with surveys in a particular organisation or region.